Light-emitting device and display device

By adopting a well-shell quantum dot structure and a suitable hole and electron transport layer in quantum dot light emitting devices, the problem of carrier transmission complexity is solved, and efficient carrier injection and long life is achieved. Improved luminous efficiency.

CN119183308APending Publication Date: 2024-12-24TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310750569.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Quantum dot light emitting devices have challenges in optimizing luminescence efficiency and lifetime, mainly due to the complex carrier transmission situation due to the differences in nanomaterials, making it difficult to simultaneously improve the efficiency and lifetime of the device.

Method used

Core-shell quantum dots with well-shell structure are used as the luminescent layer material, and are combined with hole transport layer and electron transport layer to control the shell thickness and mobility to improve carrier injection balance and efficiency.

Benefits of technology

Through this structural design, hole injection is effectively enhanced, carrier tunneling barrier is reduced, recombination efficiency is improved, exciton fluorescence life is extended, and luminescence efficiency and service life is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183308A_ABST
    Figure CN119183308A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device and a display device.The light-emitting device comprises an anode, a hole transport layer, a light-emitting layer and a cathode which are stacked, the material of the light-emitting layer comprises a core-shell quantum dot, the core-shell quantum dot comprises a plurality of shell layers, the shell layers comprise a first shell layer, a second shell layer and a third shell layer which are adjacent, the band gap of the material of the second shell layer is smaller than the band gap of the material of the first shell layer and is smaller than the band gap of the material of the third shell layer; wherein the thickness of the light-emitting layer is 1-1.5 times of the average particle size of the quantum dots; the mobility of the material of the hole transport layer is 2 * 10 <-3 >-10 * 10 <-3 > cm < 2 > / Vs. The invention aims to improve the luminous efficiency and the service life of the light-emitting device at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display, and in particular to a light-emitting device and a display apparatus. Background Art

[0002] Light-emitting devices emit light by releasing energy through the recombination of electrons and holes, and are widely used in the field of lighting. In recent years, quantum dots (QDs) have attracted widespread attention from industry, academia, and research circles due to their advantages of high fluorescence quantum yield, good monochromaticity, continuously adjustable emission spectrum with size, and strong photochemical and thermal stability. Quantum dot light emitting diodes (QLEDs) constructed with quantum dots as the light-emitting layer have become one of the most active scientific research topics due to their many advantages such as low cost, high brightness, wide color gamut, and excellent solution processability, and have shown great competitive potential in the next generation of flat panel display and solid-state lighting applications.

[0003] Although QLED display technology is inherited and developed from OLED (Organic Light-Emitting Diode), the performance of the device can be improved by applying the existing theories in OLED to QLED. However, since quantum dots are nanomaterials, when paired with other functional layers, there are huge differences in the type of material, its own structural design and film quality, the film interface injection barrier between the quantum dot material and other functional layers, and the aging and attenuation of the material itself. As a result, when different quantum dots are used in the actual processing process, completely different carrier transmission conditions will appear in the device, which aggravates the difficulty of optimizing QLED devices, making it difficult to improve the luminous efficiency and life of QLED devices at the same time, greatly limiting its development. Therefore, for quantum dot materials with large differences, it is urgent to develop more targeted high-performance light-emitting devices. Summary of the invention

[0004] In view of this, the present application provides a light-emitting device and a display device, aiming to simultaneously improve the light-emitting efficiency and service life of the light-emitting device.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present application provides a light-emitting device, comprising a stacked anode, a hole transport layer, a light-emitting layer, and a cathode, wherein the material of the light-emitting layer comprises core-shell quantum dots, the core-shell quantum dots comprise a plurality of shell layers, the plurality of shell layers comprise adjacent first shell layers, second shell layers, and third shell layers, wherein the band gap of the material of the second shell layer is smaller than the band gap of the material of the first shell layer, and smaller than the band gap of the material of the third shell layer.

[0007] Wherein, the thickness of the light-emitting layer is 1 to 1.5 times the average particle size of the quantum dots;

[0008] The mobility of the material of the hole transport layer is 2×10 -3 ~10×10 -3 cm 2 / Vs.

[0009] Optionally, in some embodiments of the present application, the HOMO energy level of the material of the hole transport layer is -5eV to -6eV; and / or,

[0010] The mobility of the material of the hole transport layer is 2.5×10 -3 ~5×10 -3 cm 2 / Vs.

[0011] Optionally, in some embodiments of the present application, the material of the hole transport layer includes at least one of TFB, V-TPAVCBP: 10% OPPI.

[0012] Optionally, in some embodiments of the present application, the average particle size of the core-shell quantum dots is 11 to 16 nm; and / or,

[0013] The external quantum efficiency of the core-shell quantum dots is greater than or equal to 70%.

[0014] Optionally, in some embodiments of the present application, the material of the first shell layer includes ZnS, the material of the second shell layer includes CdZnS, and the material of the third shell layer includes ZnS; and / or,

[0015] The core-shell quantum dot has a core, and the plurality of shell layers further include an inner shell layer located between the first shell layer and the core, and the material of the inner shell layer includes ZnSe.

[0016] Optionally, in some embodiments of the present application, the ratio of the thickness of the inner shell layer to the radius of the core of the core-shell quantum dot is 0.5 to 2:1; and / or,

[0017] The ratio of the thickness of the first shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1; and / or,

[0018] The ratio of the thickness of the second shell layer to the radius of the core of the core-shell quantum dot is 0.4 to 2:1; and / or,

[0019] The ratio of the thickness of the third shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1.

[0020] Optionally, in some embodiments of the present application, the light-emitting device further comprises an electron transport layer disposed between the cathode and the light-emitting layer, and the mobility of the material of the electron transport layer is 0.05×10 -3 ~0.5×10 -3 cm 2 / Vs.

[0021] Optionally, in some embodiments of the present application, the material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; and / or,

[0022] The average particle size of the material of the electron transport layer is 2 to 12 nm.

[0023] Optionally, in some embodiments of the present application, the core-shell quantum dot has a core, and the material of the core is selected from at least one of a II-VI group compound, an IV-VI group compound, a III-V group compound and an I-III-VI group compound; the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe , CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnS At least one of Te, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, I At least one of nNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or,

[0024] The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or,

[0025] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate, poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino] One or more of biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile.

[0026] Optionally, in some embodiments of the present application, the thickness of the anode is 20 to 200 nm; and / or,

[0027] The thickness of the cathode is 40 to 190 nm; and / or,

[0028] The thickness of the hole transport layer is 30 to 180 nm; and / or,

[0029] The thickness of the electron transport layer is 20 to 180 nm; and / or,

[0030] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, and the thickness of the hole injection layer is 20-200 nm.

[0031] In a second aspect, the present application further proposes a display device, which includes the light-emitting device described above.

[0032] In the technical solution provided in the present application, when the material used in the light-emitting layer is a core-shell structure quantum dot with a well-shell structure, the hole mobility of the matching material is 2×10 -3 ~10×10 -3 cm 2 / Vs hole transport layer can effectively enhance hole injection, improve the effective injection and efficient recombination of carriers in the device, improve the injection balance of holes and electrons, thereby improving the efficiency and life of the device; at the same time, setting the light-emitting layer as a single-layer film constructed by a single-layer quantum dot can also greatly reduce the tunneling barrier of carriers, increase the transmission rate of carriers, and help improve the recombination efficiency of carriers. Moreover, since this effect of promoting carrier injection is more prominent in promoting hole injection, it helps to further improve the injection balance of electrons and holes in the device, and then helps to simultaneously improve the luminescence efficiency and service life of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 is a schematic structural diagram of a light-emitting device proposed in one embodiment of the present application;

[0035] Figure 2 Schematic diagram of the band gap structure of a well-structured quantum dot proposed in one embodiment of the present application;

[0036] Reference numerals:

[0037] 100-light-emitting device; 10-anode; 20-light-emitting layer; 30-cathode; 40-electron transport layer; 50-hole transport layer; 60-hole injection layer; 21-quantum dot; 201-core; 202-inner shell; 203-first shell; 204-second shell; 205-third shell. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0039] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".

[0040] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0041] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0042] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0043] The present application provides a light emitting device 100, which may be a quantum dot light emitting diode (QLED) or the like. Figure 1, the light-emitting device 100 includes a stacked anode 10, a hole transport layer 50, a light-emitting layer 20 and a cathode 30, the material of the light-emitting layer 20 includes core-shell quantum dots, and the core-shell quantum dots include multiple shells. The multiple shells include adjacent first shells 203, second shells 204 and third shells 205, wherein the band gap of the material of the second shell 204 is smaller than the band gap of the material of the first shell 203, and smaller than the band gap of the material of the third shell 205. Such a shell design allows a well to be formed in the shell of the core-shell quantum dots. In this way, excess carriers in the device can be stored in the well, which plays a role in extending the fluorescence lifetime of the excitons and increasing the probability of exciton recombination. However, due to the use of a wide-bandgap shell in the well-type shell, it also causes the problem of relatively more difficult hole injection. In view of this, in the embodiment of the present application, the thickness of the light-emitting layer 20 is 1 to 1.5 times the average particle size of the quantum dots 21; the mobility of the material of the hole transport layer 50 is 2×10 -3 ~10×10 -3 cm 2 / Vs.

[0044] When the material used in the light-emitting layer 20 is a core-shell quantum dot with a well-shell structure, the hole mobility of the matching material is 2×10 -3 ~10×10 -3 cm 2 / Vs hole transport layer 50, for example, can be 2×10 -3 cm 2 / Vs, 2.5×10 - 3 cm 2 / Vs,3×10 -3 cm 2 / Vs,4×10 -3 cm 2 / Vs,5×10 -3 cm 2 / Vs,6×10 -3 cm 2 / Vs、7×10 -3 cm 2 / Vs,8×10 -3 cm 2 / Vs、9×10 -3 cm 2 / Vs,10×10 -3 cm 2 / Vs and values ​​between any two of the above values; within this range, it helps to increase hole injection, enhance the effective injection and efficient recombination of carriers in the device, and improve the injection balance of holes and electrons, thereby avoiding charging of the light-emitting layer 20 and inducing Auger recombination, which in turn affects the life and efficiency of the device.

[0045] Meanwhile, control the thickness of the light-emitting layer 20 to be 1 to 1.5 times the average particle size of the quantum dots 21. For example, it can be 1 time, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, and values between any two of the above; within this range, the prepared light-emitting layer 20 is roughly a single-layer film, which can greatly reduce the tunneling barrier of carriers, improve the transport rate of carriers, contribute to improving the recombination efficiency of carriers, and because this effect of promoting carrier injection is more prominent in promoting hole injection, it helps to further improve the injection balance of electrons and holes in the device, and further helps to simultaneously improve the light-emitting efficiency and service life of the device.

[0046] In a specific embodiment, in the core-shell quantum dots, the material of the first shell layer 203 includes ZnS, the material of the second shell layer 204 includes CdZnS, and the material of the third shell layer 205 includes ZnS; as Figure 2 shown, the bandgap of the CdZnS shell acts as a well structure because it is between the bandgaps of two adjacent ZnS shells. Specifically, ZnS is selected for the first shell layer 203 because the bandgap width of the ZnS shell is relatively wide, and as the shell component of the well-type shell layer, it can store excess electrons or holes better; for the second shell layer 204, Cd x Zn 1-x S(0<x<1) shell is selected because not only does this shell have a relatively wide bandgap itself, but also the position of its valence band is relatively moderate, which can improve the binding ability of excitons, and because the overall bandgap of this shell is narrower than that of the adjacent ZnS layer, it is very suitable to act as a well-type shell for storing excess electrons or holes; ZnS is selected for the third shell layer 205 because the bandgap width of this layer is relatively wide, and as the shell component of the well-type shell layer, it can store excess electrons or holes better; in addition, it can also provide a certain excitonic binding ability and reduce the influence of external conditions on excitons. In another specific embodiment, in the core-shell quantum dots with a well-type shell layer structure, the material of the first shell layer 203 includes ZnS, the material of the second shell layer 204 includes CdS, and the material of the third shell layer 205 includes ZnS.

[0047] In some embodiments, the core-shell quantum dots have four shell layers, and the fourth shell layer can be disposed between the core 201 and the first shell layer 203, or can be disposed outside the third shell layer 205.

[0048] In some embodiments, the core-shell quantum dot has a core 201, and the multiple shells further include an inner shell 202 located between the first shell 203 and the core 201, and the material of the inner shell 202 includes ZnSe. ZnSe has a shallow valence band, which helps to improve hole injection, and its own band gap is relatively moderate. Using it as the material of the inner shell 202 can alleviate the lattice stress of the growth of the first shell 203 to a certain extent. In a specific embodiment, the core-shell quantum dot has four shells, which are the inner shell 202ZnSe, the first shell 203ZnS, the second shell 204CdZnS and the third shell 205ZnS arranged in sequence from the inside to the outside.

[0049] In some embodiments, the ratio of the thickness of the inner shell layer 202 to the radius of the core 201 of the core-shell quantum dot is 0.5 to 2:1; for example, the ratio can be 0.5:1, 0.6:1, 0.8:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, etc.; this helps to effectively control the binding ability of excitons, which is not only beneficial to reduce the tunneling barrier during carrier injection and promote carrier injection, but also helps to effectively recombine the carriers injected into the core 201 of the quantum dot 21.

[0050] In some embodiments, the ratio of the thickness of the first shell layer 203 to the radius of the core 201 of the core-shell quantum dot is 0.02 to 0.5:1; for example, it can be 0.02:1, 0.025:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.45:1, 0.5:1, etc.; it helps to improve the shell layer's ability to store carriers while controlling the barrier for carrier tunneling to the core 201 at a lower level, thereby promoting carrier injection.

[0051] In some embodiments, the ratio of the thickness of the second shell layer 204 to the radius of the core 201 of the core-shell quantum dot is 0.4 to 2:1; for example, the ratio can be 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.3:1, 1.5:1, 1.7:1, 1.8:1, 2:1, etc.; this helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.

[0052] In some embodiments, the ratio of the thickness of the third shell layer 205 to the radius of the core 201 of the core-shell quantum dot is 0.02 to 0.5:1; for example, it can be 0.02:1, 0.025:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.45:1, 0.5:1, etc.; it helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.

[0053] In some embodiments, the core 201 material of the quantum dot 21 can be selected from but not limited to at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; as an example, the II-VI compound is selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgS At least one of Te, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from but not limited to SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe , SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from but not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, A At least one of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.

[0054] As an example, the core-shell structured quantum dots 21 may be selected from but not limited to at least one of CdZnSe / ZnSe / ZnS / CdZnS / ZnS, CdSe / ZnSe / ZnS / CdZnS / ZnS, InP / ZnSe / ZnS / CdZnS / ZnS, CdSeS / ZnSe / ZnS / CdZnS / ZnS, ZnSe / ZnSe / ZnS / CdS / ZnS, and ZnSeTe / ZnSe / ZnS / CdS / ZnS.

[0055] It should be noted that, for the material of the core 201 of the core-shell structure quantum dot or the material of the shell of the core-shell structure quantum dot, the chemical formula provided only indicates the element composition, but does not indicate the content of each element. For example, CdZnS only indicates that it is composed of three elements: Cd, Zn and S. If the content of each element is indicated, it corresponds to Cd x Zn 1-x S, 0 <x<1。

[0056] In some embodiments, the core-shell quantum dot surface is also connected to a ligand, and the raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C10-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and halide. Wherein, "substituted or unsubstituted" means that the defined group can be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group can be substituted by one or more substituents; the substituent is selected from at least one of C1-C8 alkyl, C1-C8 alkoxy and halogen; optionally, the substituent is selected from at least one of C1-C5 alkyl, C1-C5 alkoxy and halogen; or the substituent is selected from at least one of C1-C3 alkyl, C1-C3 alkoxy and halogen. The halogen refers to -F, -Cl, -Br or -I. Specifically, the organic carboxylic acid includes one or more of decadecanoic acid (CAS: 334-48-5), undecenoic acid (CAS: 112-38-9), tetradecanoic acid (CAS: 544-63-8), oleic acid (CAS: 112-80-1) and stearic acid (CAS: 57-11-4); the organic amine includes one or more of oleylamine (CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); the organic (oxygen) phosphine includes tris(II)-1-butylamine (CAS: 112-90-3) and tris(II)-1-butylamine (CAS: 124-30-1); One or more of octylphosphine (CAS: 4731-53-7) and trioctylphosphine oxide (CAS: 78-50-2); the thiol includes one or more of n-octylmercaptan (CAS: 111-88-6), dodecanethiol (CAS: 112-55-0) and octadecanethiol (CAS: 2885-00-9); the halide is selected from one or more of hydrofluoric acid, hydrochloric acid, hydroiodic acid, hydrobromic acid, metal fluoride, metal chloride, metal iodide and metal bromide.

[0057] The mass of the ligand accounts for 15% to 20% of the total mass of the quantum dots 21 and the ligand, for example, it can be 15%, 16%, 17%, 18%, 19%, 20% and values ​​between any two of the above values. Within this range, it helps to improve the dispersibility of the quantum dots 21 and enhance its film-forming effect.

[0058] In some embodiments, at least a portion of the ligands are strong coordination ligands, and the raw materials of the strong coordination ligands are selected from one or more of substituted or unsubstituted C1-C24 chain thiols and halides. The strong coordination ligands can form strong coordination bonds with the surface cations of the core-shell quantum dots, and have a low shedding rate, which helps to improve the film-forming effect of the light-emitting layer 20. Further, the mass of the strong coordination ligands accounts for 15% to 20% of the total mass of the quantum dots 21 and the ligands, for example, 15%, 16%, 17%, 18%, 19%, 20% and values ​​between any two of the above values. Within this range, when preparing the single-layer film light-emitting layer 20, the film-forming quality can be further improved.

[0059] It can be understood that the content of the ligand and the strong coordinating ligand can be detected by nuclear magnetic resonance and thermal gravimetric test, and the number of strong coordinating ligands on the surface of quantum dot 21 can be introduced during the synthesis process or by ligand exchange. First, nuclear magnetic resonance can measure the content of specific ligands on the surface of quantum dot 21. Secondly, the thermal gravimetric test can determine the total content of ligands on the surface of quantum dot 21. Finally, the difference in ligands between the two is the content of other ligands. The specific test method for determining the content of specific ligands on the surface of quantum dot 21 by nuclear magnetic resonance is as follows: dissolve quantum dot 21 in a deuterated reagent, add a specific amount of internal standard as a reference, and calculate the ratio of the chemical shift integrated area of ​​the ligand of quantum dot 21 to the chemical shift integrated area of ​​the internal standard, so as to quantify the ligand content to be measured. The thermal gravimetric test detection method is as follows: heat the quantum dot 21 material until its mass no longer changes, record the weight loss W1 of the material when it starts to lose weight to the shedding temperature of the strong coordinating ligand, and record the weight loss W2 of the material when it starts to lose weight to the time when its mass no longer changes, then W2 is the content of the ligand, and W2-W1 is the content of the strong coordinating ligand.

[0060] NMR and thermal gravimetric methods can also be used simultaneously, for example: to determine the content of specific quantum dot 21 surface ligands oleic acid (weak ligand) and thiol (thiol as a strong coordinating ligand). The specific test method is as follows: First, dissolve quantum dot 21 in deuterated toluene, use ferrocene as an internal standard (the amount added is rated, the chemical shift is 3.8-4.0ppm), and measure the chemical shift of quantum dot 21 ligand at 5.4-5.8ppm. Finally, divide the integral area of ​​the chemical shift of the ligand at 5.4-5.8ppm by the integral area of ​​the chemical shift of the internal standard at 3.8-4.0ppm to obtain the content of oleic acid ligand. Second, for example: measure the thermal gravimetric loss of quantum dot 21 at 20-600℃, and record the weight loss at 100℃-500℃, which is the total content of ligands on the surface of quantum dot 21. Finally, subtract the oleic acid ligand content from the total ligand content to obtain the thiol ligand content.

[0061] In some other embodiments, when the anions on the surface of the quantum dot 21 include sulfur atoms, for example, when the quantum dot 21 is CdS or CdZnSe / ZnSe / ZnS / CdZnS / ZnS, and the ligand is a thiol ligand, then when preparing the quantum dot 21, the thiol compound can be added as an anion source, and the S atoms on the ligand can be directly coordinated and connected with the cations on the surface of the quantum dot 21, or directly act as S atoms on the shell surface of the quantum dot 21 and be directly embedded in the shell, which helps to further improve the coordination effect of the ligand and reduce the probability of shedding.

[0062] In some embodiments, the QY of the core-shell quantum dots is ≥ 70%, for example, 70%, 75%, 80%, 85%, 90%, 92%, etc. The quantum dots 21 with higher QY have fewer defects, which helps to reduce the probability of non-radiative recombination, and high carrier injection can effectively perform efficient recombination and luminescence in the light-emitting layer 20, thereby reducing the probability of device charging and improving device performance.

[0063] In some embodiments, the average particle size of the core-shell quantum dots is 11-16 nm, for example, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, and values ​​between any two of the above values, so that it is more conducive to the quantum dots 21 to form a single layer film. Correspondingly, the thickness of the light-emitting layer 20 is 11-24 nm, for example, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 20 nm, 22 nm, 23 nm, 24 nm, and values ​​between any two of the above values.

[0064] In some embodiments, the morphology of the core-shell quantum dots includes but is not limited to sphere, cube, tetrahedron, column, tetrapod, octapod, sheet, etc.

[0065] Further, in some embodiments, in the light-emitting device 100, the material of the light-emitting layer 20 includes core-shell quantum dots with a well structure, the external quantum efficiency (QY) of the quantum dots 21 is greater than or equal to 70%, and the thickness of the light-emitting layer 20 is 1 to 1.5 times the average particle size of the core-shell quantum dots; in view of this situation, in order to improve the efficiency and life of the device, a hole transport material with a high hole injection level can be used. Specifically, the mobility of the material of the hole transport layer 50 is greater than or equal to 2×10 -3 cm 2 / Vs, and less than or equal to 10×10 -3 cm 2 / Vs to increase hole injection and improve the injection balance of holes and electrons in the device. Further, in some embodiments, the mobility of the material of the hole transport layer 50 is 2.5×10 -3~5×10 -3 cm 2 / Vs, which helps to further improve the carrier balance.

[0066] In some embodiments, the absolute value of the energy level difference between the hole transport layer 50 and the light emitting layer 20 is 0.1 to 1.6 eV, for example, 0.1 eV, 0.3 eV, 0.5 eV, 0.7 eV, 0.9 eV, 1.0 eV, 1.1 eV, 1.3 eV, 1.5 eV, 1.6 eV, and values ​​between any two of the above values. Within this energy level difference range, the hole injection barrier can be reduced, which helps to further enhance hole injection.

[0067] In some embodiments, the HOMO energy level of the material of the hole transport layer 50 is -5eV to -6eV; for example, -5eV, -5.2eV, -5.3eV, -5.4eV, -5.5eV, -5.6eV, -5.7eV, -5.8eV, -5.9eV, -6eV and values ​​between any two of the above values.

[0068] Specifically, in some embodiments, the material of the hole transport layer 50 includes at least one of TFB, V-TPAVCBP: 10% OPPI, wherein:

[0069] The Chinese name of TFB is poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)]; CAS number: 223569-31-1; HOMO energy level is -5.3 eV; hole mobility is 3×10 -3 cm 2 / Vs.

[0070] V-TPAVCBP: 10% OPPI is derived from the literature "Chemically Doped Hole Transporting Materials with Low Cross-linking Temperature and High Mobility for Solution-Processed Green / Red PHOLEDs"; HOMO level is -5.37 eV; hole mobility is 4.9×10 -3 cm 2 / Vs.

[0071] In some embodiments, the light emitting device 100 further includes an electron transport layer 40 disposed between the cathode 30 and the light emitting layer 20. The mobility of the material of the electron transport layer 40 is 0.05×10 -3 ~0.5×10 -3 cm2 / Vs, for example, 0.05×10 -3 cm 2 / Vs, 0.06×10 -3 cm 2 / Vs, 0.07×10 -3 cm 2 / Vs, 0.1×10 -3 cm 2 / Vs, 0.2×10 -3 cm 2 / Vs, 0.3×10 -3 cm 2 / Vs, 0.4×10 -3 cm 2 / Vs, 0.5×10 -3 cm 2 / Vs and values ​​between any two of the above values. Within this range, the electron injection can be precisely controlled to balance the electron injection with the hole injection in the device, thereby effectively improving the carrier balance of the device, avoiding the light-emitting layer 20 from being charged and inducing Auger recombination, thereby affecting the life and efficiency of the device.

[0072] In some embodiments, the average particle size of the material of the electron transport layer 40 is 2 to 12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 11 nm, 12 nm, and values ​​between any two of the above values. The electron transport material with such a particle size is easy to be made into a film with uniform film thickness and dense film during film formation, which helps to improve the film quality.

[0073] In some embodiments, the material of the electron transport layer 40 includes, but is not limited to, one or more of metal oxides and doped metal oxides. As an example, the metal oxide includes, but is not limited to, one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes, but is not limited to, multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes, but is not limited to, one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0074] In addition, in some embodiments, the surface of the electron transport material may be connected with a ligand, and the ligand includes one or more of an acid ligand, an amine ligand, and a thiol ligand. Specifically, the raw materials of the ligand include but are not limited to one or more of oleic acid, oleylamine, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, and octadecanoic acid.

[0075] The metal oxide MO or the doped metal oxide MAO can be obtained by mixing the cation source, the alkali source and the solvent, wherein M is a metal element and A is a doping element. Specifically, when the material to be prepared is a metal oxide, the cation source is a metal salt that can provide the M metal element, such as zinc acetate, etc.; when the material to be prepared is a doped metal oxide, the cation source includes a metal salt that can provide the M metal element and a metal salt that can provide the A doping element, such as zinc acetate, magnesium acetate, etc.; the alkali source includes one or more of an organic base and an inorganic base, the organic base is selected from one or more of hexamethylenetetramine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and urea, and the inorganic base is selected from one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, and potassium carbonate; the solvent includes alcohols or dimethyl sulfoxide (DMSO). When preparing the electron transport material, the mobility of the electron transport layer 40 material can be precisely controlled by adjusting the type and content of the doping element, the amount of alkali source added, the post-treatment conditions and other parameters. In actual operation, the preparation can be made with reference to the method for regulating the mobility of the electron transport layer 40 material commonly used in the art. Taking the method of regulating the amount of alkali source added to control the electron mobility as an example, in some embodiments, the electron transport layer 40 material is ZnO. In order to adjust its electron mobility, tetramethylammonium hydroxide can be used as the alkali source. When preparing ZnO, the molar ratio of ZnO and tetramethylammonium hydroxide is controlled to be 1:1.5, and a mobility of 0.1×10 -3 cm 2 / Vs ZnO nanoparticles; the molar ratio of ZnO and tetramethylammonium hydroxide can also be controlled to 1:0.5, and a mobility of 5×10 -3 cm 2 / Vs of ZnO nanoparticles.

[0076] In some embodiments, the anode 10 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0077] In some embodiments, the cathode 30 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0078] In some embodiments, the light-emitting device 100 further includes a hole injection layer 60 disposed between the anode 10 and the hole transport layer 50, and the material of the hole injection layer 60 includes poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)] (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tri[phenyl One or more of (m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(carbazol-9-yl)triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), and hexaazatriphenylene-capronitrile (HAT-CN).

[0079] In some embodiments, the thickness of the anode 10 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.

[0080] In some embodiments, the thickness of the cathode 30 is 40-190 nm; for example, it can be 40-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-190 nm, and the like.

[0081] In some embodiments, the thickness of the hole transport layer 50 is 30 to 180 nm; for example, it can be 30 to 40 nm, 35 to 60 nm, 50 to 80 nm, 55 to 90 nm, 70 to 100 nm, 90 to 120 nm, 110 to 140 nm, 130 to 150 nm, 140 to 170 nm, 160 to 180 nm, and the like.

[0082] In some embodiments, the thickness of the electron transport layer 40 is 20-180 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-180 nm, and the like.

[0083] In some embodiments, the thickness of the hole injection layer 60 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.

[0084] It is understandable that the light emitting device 100 may also be provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc.

[0085] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device.

[0086] Based on the above embodiments, the present application further proposes a method for preparing a light emitting device 100, which is used to prepare the above light emitting device 100. In some embodiments, the light emitting device 100 may be a positive light emitting device, and accordingly, the preparation method includes:

[0087] S10a, providing an anode 10;

[0088] S20a, sequentially disposing a hole functional layer, a light emitting layer 20 and an electron transport layer 40 on the anode 10;

[0089] S30 a , disposing the cathode 30 on the electron transport layer 40 .

[0090] In some other embodiments, the light emitting device 100 may be an inverted light emitting device, and accordingly, the preparation method includes:

[0091] S10b, providing a cathode 30;

[0092] S20b, sequentially disposing an electron transport layer 40, a light emitting layer 20 and a hole functional layer on the anode 10;

[0093] S30b, disposing the anode 10 on the electron transport layer 40 .

[0094] In steps S20a and S20b, the hole functional layer includes the hole transport layer 50 , or includes the hole transport layer 50 and the hole injection layer 60 . When the hole functional layer includes the hole transport layer 50 and the hole injection layer 60 , the hole injection layer 60 is disposed closer to the anode 10 .

[0095] In the preparation method of the light-emitting device 100, the preparation method of the anode 10, the light-emitting layer 20, the electron transport layer 40, the hole transport layer 50, the hole injection layer 60 and the cathode 30 can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip pulling, immersion, spraying, roll coating, casting, slit coating, and strip coating.

[0096] The materials of the anode 10 , the light emitting layer 20 , the electron transport layer 40 , the hole transport layer 50 , the hole injection layer 60 and the cathode 30 are as described above and will not be described in detail here.

[0097] In some embodiments, after the light emitting device 100 is prepared, the step of packaging the light emitting device 100 is further included. The packaging process can be performed by a common machine packaging or by manual packaging. Preferably, in the environment of the packaging process, the oxygen content and the water content are both less than 0.1 ppm to ensure the stability of the light emitting device 100.

[0098] In addition, the present application also relates to a display device, which includes the light-emitting device 100. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0099] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0100] Example 1

[0101] This example aims to investigate the effect of the number of quantum dot layers on device performance

[0102] Experimental Group 1

[0103] The structure of the QLED device in this experimental group is: anode, hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer and cathode stacked from bottom to top. The thickness of each layer is: anode 130nm, hole injection layer 100nm, hole transport layer 90nm, quantum dot light-emitting layer 12nm, electron transport layer 60nm, cathode 60nm.

[0104] (1) A glass substrate is provided, and ITO is evaporated on the glass substrate to form an anode.

[0105] (2) Spin coating a PEDOT:PSS material (a commercial product with a doping ratio of 1:6 and a solute content of 1.5 wt%) on the anode and heating at 150° C. for 15 min to obtain a hole injection layer.

[0106] (3) The substrate prepared in step (2) was transferred to a nitrogen atmosphere, and a hole transport material was spin-coated on the hole injection layer, and heated at 150° C. for 15 min to obtain a hole transport layer; wherein the hole transport material was TFB, and its HOMO energy level was −5.3 eV and its mobility was 3×10 -3 cm 2 / Vs.

[0107] (4) Spin coating an octane solution of a quantum dot material on the hole transport layer, and heating at 80° C. for 10 min to obtain a quantum dot light-emitting layer; wherein the quantum dot material includes blue quantum dots CdZnSe / ZnSe / ZnS / CdZnS / ZnS, with a QY of 80%, an average particle size of 12 nm, a surface ligand of octanethiolan, a mass content of octanethiolan on the surface of the quantum dots of 16%, and a ratio of the thickness of the inner shell layer ZnSe to the core radius of 1:1, a ratio of the thickness of the first shell layer ZnS to the core radius of 0.2:1, a ratio of the thickness of the second shell layer CdZnS to the core radius of 1.5:1, and a ratio of the thickness of the third shell layer ZnS to the core radius of 0.2:1; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the octane solution of the quantum dot material is 10 mg / ml, so as to control the quantum dot light-emitting layer to be a single layer film.

[0108] (5) Spin-coating an ethanol solution of an electron transport material with a concentration of 30 mg / ml on the quantum dot light-emitting layer and heating at 100° C. for 8 min to obtain an electron transport layer; wherein the electron transport material is ZnO, and its electron mobility is 0.1×10 -3 cm 2 / Vs; the electron mobility is 0.1×10 -3 cm 2 / Vs ZnO preparation method is: weigh 1mmol Zn(Ac)2·2H2O and 10ml DMSO into a three-necked flask, and then stir at 25℃ until completely dissolved to obtain a first solution; dissolve 1.5mmol tetramethylammonium hydroxide in 10ml ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain an electron mobility of 0.1×10 -3 cm 2 / Vs of ZnO nanoparticles.

[0109] (6) Placing the substrate obtained in step (5) in a vapor deposition chamber, vapor-depositing Ag on the electron transport layer to obtain a cathode, and encapsulating to obtain a QLED device.

[0110] Control group 1

[0111] The scheme of control group 1 is basically the same as that of experimental group 1, except that in this control group, the quantum dot luminescent layer is a double-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 12 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 20 mg / ml, so as to control the quantum dot luminescent layer to be a double-layer film. The other steps and parameters are the same as those of experimental group 1.

[0112] Control group 2

[0113] The scheme of control group 2 is basically the same as that of experimental group 1, except that in this control group, the quantum dot luminescent layer is a four-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 12 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 35 mg / ml, so as to control the quantum dot luminescent layer to be a four-layer film. The other steps and parameters are the same as those of experimental group 1.

[0114] (i) Take the semi-finished device obtained in step (4) during the preparation of experimental group 1, control group 1 and control group 2, wherein the top layer of the semi-finished device is the light-emitting layer. The roughness of the light-emitting layer is examined by AFM to evaluate its film-forming effect, and the results are recorded in Table 1.

[0115] (ii) Prepare the corresponding single carrier devices of experimental group 1, control group 1 and control group 2 respectively, and test the current density-voltage curve of the single carrier transport thin film device (HOD / EOD). Take the current density of the device at a constant voltage of 8V for comparison. Among them:

[0116] The preparation method of the single electron device (EOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the hole injection layer and the hole transport layer are subtracted.

[0117] The preparation method of the single hole device (HOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the electron transport layer is subtracted.

[0118] The results are recorded in Table 1.

[0119] (III) Take the devices made in experimental group 1, control group 1 and control group 2, and place the devices under 120°C for 15 minutes for heat treatment to accelerate the forward aging of the devices. Then, perform subsequent performance tests on the devices after the heat treatment, and record the results in Table 1. The detection method is as follows:

[0120] (1) The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:

[0121]

[0122] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0123] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0124] (2) The test method for life T95@1000nit is:

[0125] The time required for the device to reduce its brightness to a certain percentage of the maximum brightness when driven by a constant current or voltage. The time it takes for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life under 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:

[0126]

[0127] Among them, T95 L For lifespan at low brightness, T95 His the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of blue QLED devices at rated brightness and found that the A value was 1.7.

[0128] Table 1

[0129]

[0130]

[0131] As can be seen from the table above, the roughness of experimental group 1 is similar to that of the control group, indicating that a single-layer film can have a good film-forming effect. However, compared with the control group, experimental group 1 has higher EQE and T95 1000nit , and at 8V, the current density of the HOD device and the EOD device is not only larger, but also closer, indicating that when the luminescent layer material uses a core-shell structure quantum dot with a QY greater than or equal to 70% and a well-shell structure, the hole transport layer uses a hole transport material with high hole injection, and the electron transport layer uses a low conduction band electron transport material, compared with a double-layer film or a multi-layer film, the carrier injection in the single-layer film quantum dot luminescent layer is more balanced, showing a significantly longer service life. This shows that the single-layer film is more compatible with the above-mentioned matching design, which helps to significantly improve the life of the device while ensuring the luminous efficiency.

[0132] Example 2

[0133] This example aims to investigate the effect of the quantum dot shell structure on device performance.

[0134] The schemes of experimental group 2 and control groups 2 to 4 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot materials used in the quantum dot light-emitting layer are changed to the materials listed in Table 2 below.

[0135] Performance tests were performed on experimental groups 1-2 and control groups 2-4, and the results are recorded in Table 2.

[0136] Table 2

[0137]

[0138]

[0139] It can be seen from the above table that for devices using the same hole transport layer and electron transport layer design, when the shell structure of the quantum dot light-emitting layer material is changed from the well structure ZnSe / ZnS / CdZnS / ZnS or the well structure ZnSe / ZnS / CdS / ZnS to other non-well shell structures, the device life is greatly reduced. This shows that compared with other shell structures, the well shell structure design is better matched with the device hole transport layer and electron transport layer.

[0140] Example 3

[0141] This example aims to investigate the effect of quantum dot shell thickness on device performance.

[0142] This embodiment also sets up control groups 5 to 8. Among them:

[0143] The schemes of control groups 5 to 8 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot material used in the quantum dot light-emitting layer is changed to the material with the thickness of each shell layer defined in Table 3 below.

[0144] Performance tests were performed on experimental group 1 and control groups 5 to 8, and the results are recorded in Table 3.

[0145] Table 3

[0146]

[0147] It can be seen from the table above that with the change of the thickness of each shell layer, the EQE and T95 of each group of devices 1000nit There have been significant changes. For the well-shell quantum dots with a shell structure of ZnSe / ZnS / CdZnS / ZnS in the single-layer quantum dot luminescent layer, the thickness of the well-shell layer plays an important role in the efficient injection of electrons and holes into the quantum dot core; further, compared with the control groups 5-8, the experimental group 1 showed higher EQE and T95 1000nit , indicating that the shell thickness design scheme proposed in this application is better and significantly improves the EQE and life of the device.

[0148] Example 4

[0149] This example aims to investigate the effect of hole transport materials on device performance.

[0150] This embodiment also sets up experimental group 3, experimental group 4, and control groups 9 to 12. Among them:

[0151] The experimental group or control group scheme is basically the same as that of experimental group 1, except that in each experimental group or control group, the hole transport material used in the hole transport layer is changed to the material in Table 4 below.

[0152] Performance tests were performed on experimental groups 1, 3, 4 and control groups 9-12, and the results are recorded in Table 4.

[0153] Table 4

[0154]

[0155] It can be seen from the above table that the experimental group exhibits higher luminous efficiency and lifespan than the control group, indicating that the materials provided by the experimental group are more compatible with the device provided in this embodiment than the four materials provided by the control group. Obviously, for the single-layer film luminescent layer prepared by using quantum dots with QY greater than or equal to 70% and shell layer of ZnSe / ZnS / CdZnS / ZnS, and the material with electron mobility of 0.05×10 -3 ~0.5×10 -3 cm 2 / Vs for the device with electron transport layer, the hole mobility of the hole transport material used is 2×10 -3 ~10×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.

[0156] Example 5

[0157] This example aims to investigate the effect of the mobility of the electron transport material on the device performance.

[0158] This embodiment further sets up a control group 13 and a control group 14. Among them:

[0159] The control group scheme is basically the same as the experimental group 1, the only difference is that in each control group, the electron transport material used in the electron transport layer is changed to the material in the following Table 5.

[0160] The mobility is 0.01×10 -3 The preparation method of ZnMgO is as follows: weigh 0.9mmol Zn(Ac)2·2H2O, 0.1mmol Mg(Ac)2·4H2O and 10ml DMSO into a three-necked flask, and then stir at 25°C until completely dissolved to obtain a first solution; dissolve 1.5mmol tetramethylammonium hydroxide in 10ml ethanol to obtain a second solution; then slowly drop the second solution into the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain ZnMgO nanoparticles.

[0161] The mobility is 2×10 -3The preparation method of ZnO is as follows: compared with experimental group 1, the only difference is that the molar ratio of Zn(Ac)2·2H2O and tetramethylammonium hydroxide is changed to 1:0.8.

[0162] Performance tests were performed on experimental group 1, control group 13 and control group 14, and the results are recorded in Table 5.

[0163] Table 5

[0164]

[0165]

[0166] It can be seen from the above table that compared with the control group, the experimental group exhibits higher luminous efficiency and lifespan, indicating that compared with the four materials provided by the control group, the electron transport material provided by the experimental group is more compatible with the device provided in this embodiment. Obviously, for the single-layer film luminescent layer prepared by using quantum dots with QY greater than or equal to 70% and shell layer of ZnSe / ZnS / CdZnS / ZnS, and the hole mobility of the material is 2.0×10 -3 cm 2 / Vs~10×10 -3 cm 2 For devices using hole transport materials with a hole transport layer of 0.05×10 -3 ~0.5×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.

[0167] The light-emitting device and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A light emitting device, characterized in that: A method for manufacturing a semiconductor device comprising a stacked anode, a hole transport layer, a light-emitting layer and a cathode, wherein the material of the light-emitting layer comprises core-shell quantum dots, the core-shell quantum dots comprise a plurality of shell layers, the plurality of shell layers comprise adjacent first shell layers, second shell layers and third shell layers, wherein the band gap of the material of the second shell layer is smaller than the band gap of the material of the first shell layer, and smaller than the band gap of the material of the third shell layer; Wherein, the thickness of the light-emitting layer is 1 to 1.5 times the average particle size of the quantum dots; The mobility of the material of the hole transport layer is 2×10 -3 ~10×10 -3 cm 2 / Vs.

2. The light emitting device according to claim 1, characterized in that: The HOMO energy level of the material of the hole transport layer is -5eV to -6eV; and / or, The mobility of the material of the hole transport layer is 2.5×10 -3 ~5×10 -3 cm 2 / Vs.

3. The light emitting device according to claim 2, characterized in that: The material of the hole transport layer includes at least one of TFB, V-TPAVCBP: 10% OPPI.

4. The light emitting device according to claim 1, characterized in that: The average particle size of the core-shell quantum dots is 11 to 16 nm; and / or, The external quantum efficiency of the core-shell quantum dots is greater than or equal to 70%.

5. The light emitting device according to claim 1, characterized in that: The material of the first shell layer includes ZnS, the material of the second shell layer includes CdZnS, and the material of the third shell layer includes ZnS; and / or, The core-shell quantum dot has a core, and the plurality of shell layers further include an inner shell layer located between the first shell layer and the core, and the material of the inner shell layer includes ZnSe.

6. The light emitting device according to claim 5, characterized in that: The ratio of the thickness of the inner shell layer to the radius of the core of the core-shell quantum dot is 0.5 to 2:1; and / or, The ratio of the thickness of the first shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1; and / or, The ratio of the thickness of the second shell layer to the radius of the core of the core-shell quantum dot is 0.4 to 2:1; and / or, The ratio of the thickness of the third shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:

1.

7. The light emitting device according to claim 1, characterized in that: The light emitting device further comprises an electron transport layer disposed between the cathode and the light emitting layer; The mobility of the material of the electron transport layer is 0.05×10 -3 ~0.5×10 -3 cm 2 / Vs.

8. The light emitting device according to claim 1, characterized in that: The material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; and / or, The average particle size of the material of the electron transport layer is 2 to 12 nm.

9. The light emitting device according to claim 1, characterized in that: The core-shell quantum dots have a core, the material of the core is selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnS e, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS , PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, At least one of InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or, The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or, The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate, poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino] One or more of biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile.

10. A display device, characterized in that: The display device comprises the light emitting device according to any one of claims 1 to 9.